Formation and management of the client base of banking institutions - Luan Qiuxia (Kharkiv : V. N. Karazin Kharkiv national university, 2024)
The object of research is the economic relations that arise in the process of forming and managing a bank's client base. The subject of research includes the scientific and methodological support and practical tools for managing the client base within the framework of a bank's clientoriented strategy. The purpose of the master's thesis is to improve the theoretical foundations and scientific-methodological approaches to the formation and management of a bank's client base. Theoretical provisions, conclusions, and practical recommendations provided in the research create a foundation for effectively managing the client base within the framework of a client-oriented strategy for banks. Practical significance: The research provides actionable insights and methodologies that JSC "Oschadbank" can implement to optimize its client base management system, enhance customer satisfaction, and strengthen its competitive position in the financial market.
Scientific advisor: Morozova N., PhD in economics, associate professor, department management, business and professional communications
Keywords: SOCIAL SCIENCES::Social sciences; management; bank; client base of the bank; formation of client base; development of client base; management of relations with clients